The safety and efficacy of dabrafenib and trametinib for the treatment of melanoma. Issue 1 (2nd January 2018) - Knispel, Sarah; Zimmer, Lisa; Kanaki, Theodora; Ugurel, Selma; Schadendorf, Dirk; Livingstone, Elisabeth
ABSTRACT: Introduction : The introduction of BRAF and MEK inhibitors into clinical practice improved the prognosis of metastatic melanoma patients. The combination of BRAF inhibitor dabrafenib with MEK inhibitor trametinib has shown its superiority to single agent therapy and is characterized by a tolerable spectrum of adverse events which shows a decrease in incidence over time on treatment. Areas covered : The current scientific literature on safety and adverse events (AEs) related to BRAF and MEK-inhibition has been investigated with special focus on the large phase 3 studies (COMBI-v, COMBI-d and CoBRIM) as well as recent updates presented at oncology and melanoma meetings. Additionally, published case series/case reports were screened for information on AEs. Expert opinion : Even though almost every patient (98%) under combination therapy with dabrafenib and trametinib experiences at least one adverse event, these are generally mild to moderate, reversible and can be managed with dose reductions or interruptions. However, due to an increased life expectancy, there is a substantial need to prevent and treat also mild adverse events, as they play a central role for the quality of life of patients. Ongoing clinical trials will have to demonstrate the efficacy as well as safety of triple combination with anti-PD-1/anti-PD-L1 antibodies.